Sistem Kendali Jarak Jauh Berbasis Mikrokontroler AVR ATmega 8535 di Pabrik Kelapa Sawit - Ahmad Mahfud (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
Advances in automation technology have begun to be implemented in the palm oil industry in an integrated manner. The current existence of the Palm Oil Mill is an obstacle in terms of monitoring its operations. Work processes that are heavily dependent on the performance of each worker, cause the level of variability in work is very high. The need for a monitoring system on the performance of ongoing processing in real time, strongly supports the achievement of parameters and standards set at the Palm Oil Mill. A supervisor desperately needs a monitoring system capable of functioning as a control system in order to access mill performance remotely, so that he can monitor the performance of every machine that is very large and far from a large area, and can be monitored and controlled quickly from same location. In this research will be applied AVR AT ATmega 8535 mikrokontroler as controller of equipment object that can be controlled from long distance. By using the USB interface to Serial Converter as well as Laptop and Gadget devices connected to the internet, he will be able to monitor and control the operation of an equipment object. Utilization of AVR AT ATmega 8535 is possible to be developed for a more complex control system. Visualization for a more attractive and user-friendly control system can be made by using Delphi 7 software.